Physical activity behaviour in patients with metabolic syndrome (Swiss Medical Weekly, 2012)
STUDY/PRINCIPLES: Physical activity improves the clinical course of the metabolic syndrome and its risk factors. The aim of this study was to investigate the physical activity behaviour in patients with metabolic syndrome in regard to the recommendation of the Federal Offices of Public Health (BAG) and Sports (BASPO): “to exercise half an hour a day  at a medium intensity.” METHODS: 47 patients with metabolic syndrome were recruited from the Outpatient Department of the Division of Internal Medicine of the University Hospital Zurich. 24 patients were included and physical activity behaviour was assessed by using the International Physical Activity Questionnaires. RESULTS: All of the patients knew about the positive effect of physical activity on the course of the metabolic syndrome although 62% of the patients (n = 15) had no knowledge of the BAG/BASPO recommendations. 54% of the patients (n = 13) performed physical activity in accordance to the recommendation with or without knowing the recommendations. Most of the patients (n = 21, 87%) were motivated to improve their physical activity, but missing opportunities and instructions were important reasons for not being physically active. CONCLUSION: Patients with metabolic syndrome usually know about the positive effect of physical activity on the course of their disorder and are motivated to improve physical activity behaviour. However, the BAG/BASPO recommendations are not widely known and should therefore become more popular and better communicated particularly to patients with metabolic syndrome. Furthermore, patients have to be supported and instructed practically how to get physically active in accordance with their co-morbidities.